Additional Feeding with The Basic Ingredients of Moringa Oleifera for Pregnant Women to Overcome Stunting - Sherly Puspita Dhani; Novalya Irma Putri; Rusfira Rusfira; Sufyan Anwar (Journal of Nutrition Science, 2022)
The rate of stunting in Indonesia is still very high. Based on the results of the Basic Health Research (Riskesdas) shows that the prevalence of stunting in 2018 shows that the rate of stunting in children under five in Indonesia reaches 30.8%. Stunting is caused by many factors, such as the effect of the condition by the mother during pregnancy. In addition, indirect factors such as exclusive breastfeeding, mother's knowledge, and economic factors also affect the health of toddlers. This literature review aims to identify a number of studies on Supplementary Feeding (PMT) made from Moringa Oleifera in pregnant women to overcome stunting. Moringa Oleifera can be used as an alternative source of protein and calcium that is potential to sufficient the nutritional needs of pregnant. The articles using Google and Google Scholar as seeking.